Perceived fairness in the taxation of a digital business model - Stefan Greil; Christian Schwarz; Stefan Stein (Hochschule Düsseldorf, Fachbereich Wirtschaftswissenschaften, 2018)
The "fair" taxation of digital business models is challenging. One of the key aspects - both policy makers and the public opinion consider as most pressuring - is the determination of intragroup transfer prices for intangibles used in digital business models. In this paper, we address the issue of a "perceived fair" taxation of the digital economy in the light of the arm's length principle based on a survey with transfer pricing experts. The aim of the survey is not to estimate arm's length profit allocations but rather to elicit fairness considerations in different transfer pricing related scenarios. In a digital economy framework where arm's length profits are distributed extremely inequitably, subjects perceive this distribution of profits as most unfair compared to more balanced scenarios. Consequently, subjects propose a "fair" distribution of profits that substantially differs from the exogenously given arm's length allocation. In scenarios with a more balanced arm's length allocation of profits, we find that the perceived fairness for the expert groups increases while a control group of business students is almost not influenced by the arm's length allocation of profits. – – Die "faire" Besteuerung digitaler Geschäftsmodelle ist herausfordernd. Einer der Schlüsselaspekte ist dabei die Ermittlung konzerninterner fremdvergleichskonformer Verrechnungspreise für immaterielle Vermögenswerte, die verstärkt in digitalen Geschäftsmodellen genutzt werden. Dieser Beitrag beschäftigt sich mit der "wahrgenommenen" Fairness bei der Besteuerung digitaler Geschäftsmodelle vor dem Hintergrund des Fremdvergleichsgrundsatz. Grundlage hierfür ist eine Umfrage unter Verrechnungspreis-Experten (Finanzbeamte und Steuerberater). Wir finden, dass wenn der Fremdvergleichsgrundsatz zu einer sehr ungleichen Verteilung des Steuersubstrats führt, die Teilnehmer diese Gewinnverteilung im Vergleich zu ausgewogeneren Szenarien als unfair erachten. Dementsprechend zeigen unsere Ergebnisse, dass zwar der Fremdvergleichsgrundsatz als Referenzpunkt für Fairness Überlegungen dient. In Bezug auf die individuell vorgeschlagene faire Gewinnverteilung können aber erhebliche Unterschiede zur fremdvergleichskonformen Gewinnverteilung bestehen.
urn:nbn:de:hbz:due62-opus-15759
Keywords: D90; F23; H25; H26; K34; 650; corporate income tax; profit-shifting; arm's length principle; fairness; digital economy